Quantitative Proton Spectroscopy of the Testes at 3 T: Toward a Noninvasive Biomarker of Spermatogenesis. Issue 2 (February 2018) - Storey, Pippa; Gonen, Oded; Rosenkrantz, Andrew B.; Khurana, Kiranpreet K.; Zhao, Tiejun; Bhatta, Rajesh; Alukal, Joseph P.
Abstract : Objectives: The aim of this study was to compare testicular metabolite concentrations between fertile control subjects and infertile men. Materials and Methods: Single voxel proton magnetic resonance spectroscopy ( 1 H-MRS) was performed in the testes with and without water suppression at 3 T in 9 fertile control subjects and 9 infertile patients (8 with azoospermia and 1 with oligospermia). In controls only, the T1 and T2 values of water and metabolites were also measured. Absolute metabolite concentrations were calculated using the unsuppressed water signal as a reference and correcting for the relative T1 and T2 weighting of the water and metabolite signals. Results: Testicular T1 values of water, total choline, and total creatine were 2028 ± 125 milliseconds, 1164 ± 105 milliseconds, and 1421 ± 314 milliseconds, respectively (mean ± standard deviation). T2 values were 154 ± 11 milliseconds, 342 ± 53 milliseconds, and 285 ± 167 milliseconds, respectively. Total choline concentration was lower in patients (mean, 1.5 mmol/L; range, 0.9–2.1 mmol/L) than controls (mean, 4.4 mmol/L; range, 3.2–5.7 mmol/L; P = 4 × 10 −5 ). Total creatine concentration was likewise reduced in patients (mean, 1.1 mmol/L; range, undetectable −2.7 mmol/L) compared with controls (mean, 3.6 mmol/L; range, 2.5–4.7 mmol/L; P = 1.6 × 10 −4 ). The myo -inositol signal normalized to the water reference was also lower in patients than controls ( P = 4 × 10 −5 ). Conclusions: Testicular metabolite concentrations, measured by proton spectroscopy at 3 T, may be valuable as noninvasive biomarkers of spermatogenesis.